A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia - Stubbs, Alexander L.; Karin, Benjamin R.; Arifin, Umilaela; Iskandar, Djoko T.; Arida, Evy; Reilly, Sean B.; Bloch, Luke M.; Kusnadi, Agus; Mcguire, Jimmy A. (Zootaxa, 2017)
Lepidodactylus pantai is a new species of gecko from the Kei Islands, Maluku, Indonesia that is closely associated with intertidal habitats. This species does not fit cleanly into any of the three species groups described for the genus because it possesses the unique combination of both divided terminal scansors on all toes and a nearly completely cylindrical tail without fringes or evidence of dorsoventral compression. A phylogenetic analysis including this species demonstrates that it is the sister taxon of a population from Palau, and that this clade is sister to the clade containing Group III species for which we have molecular data.